(untitled) - Jacobs, Linda (New York, N.Y., 1986)
This document was developed in response to the need for simplified technical information for planning environmentally sound small-scale projects in third world countries. It is aimed specifically at those who are planning or managing small-scale livestock projects in less-developed areas of the tropics and sub-tropics. The guidelines included in the manual stress: Ecological principles that relate to livestock production; The role of livestock in the local farming system; Environmental factors that affect the success of a livestock project; and Environmentally sound livestock management practices. Specific chapters in the book deal with basic ecological principles, planning, livestock characteristics, the soil and its nutrient cycles, management of wastes and nutrients, health and husbandry, agricultural systems, and making the planning process work
Keywords: Livestock projects,Livestock projects,Livestock; Planning,Handbooks, manuals, etc.,Environmental aspects,Handbooks, manuals, etc.,Ecology,Handbooks, manuals, etc